Current status, prospect and policy and institutional support for Conservation Agriculture in the Asia-Pacific region - Kassam, A.; Hongwen, Li; Niino, Y.; Friedrich, Theodor; Jin, He; Xianliang, Wang (International Journal of Agricultural and Biological Engineering, 2014)
The current growing demand for Conservation Agriculture (CA) at the national level in the countries of the Asia-Pacific region presents an opportunity to promote its widespread adoption and up-scaling through national policy and institutional support that appears necessary. Despite the obvious benefits of CA, it does not spread automatically unless the constraints that hinder adoption are understood and addressed in specific situations. These can include a combination of intellectual, social, financial, biophysical, technical, infrastructure constraints, or policy related support. Knowing what the bottlenecks are is important in developing strategies to overcome them. This paper presents: (a) some of the generic policy opportunities that exist for the adoption and uptake of CA; (b) a summary proceedings and outcome of the Regional Expert Consultation Workshop held in Beijing and sponsored by FAO Regional Office for Asia-Pacific which describes the status of CA in the Asia-Pacific region; (c) the challenges to CA adoption and uptake in the Asia-Pacific region; and (d) the conditions that need to be taken into account in designing and promoting policy and institutional support strategies for up-scaling CA.Keywords: Conservation Agriculture, policy and institutional support, adoption, Asia-Pacific region, tillage, agricultural mechanization, CA alliance, institutional cooperationDOI: 10.3965/j.ijabe.20140705.001Citation: Kassam A, Li H W, Niino Y, Friedrich T, He J, Wang X L. Current status, prospect and policy and institutional support for conservation agriculture in the Asia-Pacific region. Int J Agric & Biol Eng, 2014; 7(5): 1－13.